GENETIC PARALLELS IN PERIVENTRICULAR LEUKEMATOGRAPHY IN NEWBORNS - Sayfutdinova, Sayyora (International Journal of Psychosocial Rehabilitation, 2020)
The use of modern technologies in perinatal practice has made it possible to clarify the etiology, pathogenetic mechanisms of the development of periventricular leukemalacia (PVL), we believe it is possible that genetic variants of coagulation factors may play a role in the development of certain states of the disease in children born with low weight.